Synthesis, Structural Investigations and Antimicrobial Activities of Homo Binuclear Complexes Derived from 2-Amino-4-chlorophenol - Savitha, K.; Vedanayaki, S. (Asian Journal of Chemistry, 2020)
Co(II), Ni(II) and Cu(II) homo binuclear Schiff base metal complexes were synthesized from terephthalaldehyde and 2-amino-4-chlorophenol in methanol using template method. The structure of the ligand and its metal complexes were established by elemental, molar conductance, UV, magnetic moment, IR, 1H & 13C NMR, EPR, mass, thermal and PXRD. Molar conductance values showed that all complexes were non-electrolytic in nature. The IR spectral data provides the coordination of azomethine nitrogen and oxygen with central metal ion. UV, ESR and magnetic moment values suggest square planar geometry for Co(II), Ni(II) and Cu(II) complexes. TGA and DSC analysis data show the thermal stability of the ligand and its metal complexes. The crystalline nature of ligand and its metal complexes were investigated by powder-XRD. The DNA cleavage activities of all the complexes assayed on PUC18 DNA shows nuclease ability.